2002
DOI: 10.1021/jp025943s
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Exchange Reactions Yield Subnanometer, Thiol-Stabilized Gold Particles with Defined Optical Transitions

Abstract: A convenient preparation is reported for a series of functionalized, thiol-stabilized gold particles with subnanometer core diameters (d CORE ) 0.8 ( 0.2 nm). The preparation produces previously inaccessible materials through ligand exchange reactions of a phosphine-stabilized precursor, Au 11 (PPh 3 ) 8 Cl 3 , with ω-functionalized alkanethiols. Convenient access to these new materials is a prerequisite to the detailed study of the electronic and optical properties of subnanometer particles and the investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
238
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(256 citation statements)
references
References 39 publications
17
238
1
Order By: Relevance
“…Despite the documented potentiality of these systems, [8] the development of reliable direct synthetic protocols for the synthesis of stable and lipophilic AuNPs characterized both by very small core diameter and potential recognition properties of the organic shell still remains a challenging task. [9] The combination of these features could indeed lead to the manufacture of nanoscale devices with potential applications as sensors, switches, and new materials that have tunable properties.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the documented potentiality of these systems, [8] the development of reliable direct synthetic protocols for the synthesis of stable and lipophilic AuNPs characterized both by very small core diameter and potential recognition properties of the organic shell still remains a challenging task. [9] The combination of these features could indeed lead to the manufacture of nanoscale devices with potential applications as sensors, switches, and new materials that have tunable properties.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of Au 11 was revealed to be an incomplete icosahedral skeleton with an approximately C 3v symmetry by single crystal X-ray diffraction by various research groups. [1,2,10,12] Recently, it was found that the number of phosphine can be eight, too, when triphenyl phosphine was employed to protect the Au 11 core, [9,11] and the formula was determined to be Au 11 -A C H T U N G T R E N N U N G (PPh 3 ) 8 Cl 3 by electrospray ionization mass spectrometry (ESI), thermogravimetric analysis (TGA), elemental analysis, etc. In both cases (i.e., Au 11 …”
mentioning
confidence: 99%
“…Therefore, general pathways for pure metal functionalization may lead to unstable bonds that can be impaired through the input of thermal, chemical or electrical energy 221,222 . Pure metal nanoparticles have been successfully functionalized with thiols 204,223,224 , di-sulfides 200 , amines 223,[225][226][227] , nitriles, carboxylic acids and phosphines 225,226,228 . Selected examples will be presented in the following sections.…”
Section: Chemistry On Pure Metal Surfacesmentioning
confidence: 99%
“…This procedure is interesting for the functionalization of nanostructured surfaces where the organic function to be introduced is not compatible with the synthesis conditions of the pure metal surface 239 . The stability of thiols is limited and thiols were shown to desorb during aging in biological media 224,240 , which was directly related to the electronic structure of the metal particle core 228 .…”
Section: Thiols and Di-sulfidesmentioning
confidence: 99%